2013
DOI: 10.1177/0731684413494108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and structural properties of a novel melt processed PET–hemp composite: Influence of additives and fibers concentration

Abstract: The mechanical and structural properties of novel melt processed poly-ethylene terephthalate (PET)-hemp fiber composites for engineering applications were investigated. First, four reinforcement formulations were compared with the PET modified with poly-epsilon-caprolactone: hemp, Clay/hemp, pyromellitic dianhydride/hemp and glycidyl methacrylate/hemp. Next, the effect of hemp fibers concentration as well as the effect of heat treatment was analyzed. A significant difference was observed in the mechanical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
(34 reference statements)
3
4
0
Order By: Relevance
“…In this regard, for all of the applied heating rates, the E a of the second thermodegradation step increased with the fiber concentration until a maximum value was reached; this was followed by a gradual decrease. Such behavior was similar to the variation of the elastic modulus of the same formulations, which were reported in a previous work.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In this regard, for all of the applied heating rates, the E a of the second thermodegradation step increased with the fiber concentration until a maximum value was reached; this was followed by a gradual decrease. Such behavior was similar to the variation of the elastic modulus of the same formulations, which were reported in a previous work.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the data suggested a lower moisture absorption by the composite formulations; this was either due to the hemp fibers’ alkaline treatment or possible hydrogen bonding between the hydroxyl groups of the fibers and the carbonyl groups of PET. The latter hypothesis, which was verified earlier with the mechanical properties of the investigated composites, was also the motivation for the processing without the use of coupling agents.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Among the findings reported so far on natural fibre reinforced high temperature engineering plastics such as date palm leaf fibre/recycled poly(ethylene terephthalate), PET/Hemp, Jute fabric/polyamide and empty fruit bunch fibre/recycled poly(ethylene terephthalate), it was observed that the processing temperature of the natural fibre reinforced thermoplastics is highly dependent on the thermal degradation temperature of the natural fibres since the maximum processing temperature for natural cellulose-based fibres occurs at around 200°C. [1][2][3][4] Above this temperature, there is usually thermal degradation of natural fibres and consequently the decrease in mechanical properties of the resultant composite. [5][6][7] As a result, other natural fibre/fabric such as leather is being considered.…”
Section: Introductionmentioning
confidence: 99%
“…These properties include, but are not limited to, thermal degradation kinetics [27], mechanical (elastic modulus, tensile strength and modulus), thermo-physical (degradability) and structural [28], among others as well as cyclic and creep [29] and mechanical (3-pont flexural and monotonic tensile) [30]. For examples, the experimental work carried out by Talla et al [31] highlighted the effects of hemp fiber reinforcement on the mechanical and structural properties of polyethylene terephthalate (PET)-hemp fiber composite samples. They concluded that addition of additives increased the mechanical properties (elastic modulus and strain at break) of the concerned composite samples.…”
Section: Introductionmentioning
confidence: 99%